Skeletons in the closet? Using a bibliometric lens to visualise phytochemical and pharmacological activities linked to Sceletium, a mood enhancer - Reddy, Kaylan; Stafford, Gary I.; Makunga, Nokwanda P. (Frontiers in Plant Science, 2024)
Plants from the Sceletium genus (Aizoaceae) have been traditionally used for millenia by the Khoe and Khoen people in southern Africa, as an appetite suppressant and mood elevator. In recent times, Sceletium has been commercialised in the South African natural products industry. The research on this species has seen rapid growth with advancements in analytical and pharmacological tools to better understand the composition and bioactivity. The Web of Science database was searched for articles related to ‘Sceletium’ and ‘Mesembrine’. These data were analysed using the VOSviewer software to generate term maps and author associations. Thematic areas with the most citations were, South African Traditional Medicine for mental health (110) and anxiolytic agents (75). Pioneer studies focused on chemical structural isolation, purification and characterization. Techniques such as thin layer chromatography, liquid chromatography-mass spectrometry, gas chromatography-mass spectrometry, and nuclear magnetic resonance to study mesembrine alkaloids. Different laboratories have used a diverse range of extraction and pre-analytical methods that become routinely favoured in the analysis of the main metabolites (mesembrine, mesembranol, mesembranone and Sceletium A4) in their respective experimental settings. In contrast with previous reviews, this paper identified gaps in the research field, being a lack of toxicology assays, a deficit of clinical assessments, too few bioavailability studies and little to no investigation into the minor alkaloid groups found in Sceletium. Future studies are likely to see innovations in analytical techniques like leaf spray mass spectrometry and direct analysis in real-time ionization coupled with high-resolution time-of-flight mass spectrometry (DART-HR-TOF-MS) for rapid alkaloid identification and quality control purposes. While S. tortuosum has been the primary focus, studying other Sceletium species may aid in establishing chemotaxonomic relationships and addressing challenges with species misidentification. This research can benefit the nutraceutical industry and conservation efforts for the entire genus. At present, little to no pharmacological information is available in terms of the molecular physiological effects of mesembrine alkaloids in medical clinical settings. Research in these fields is expected to increase due to the growing interest in S. tortuosum as a herbal supplement and the potential development of mesembrine alkaloids into pharmaceutical drugs.